Double Limberg Flap for Stage IV Sacral Decubitus Ulcers with Compression Fracture of the First Vertebra of Lumbar Spine: A Case Report - Rafki Haris; Wiria Aryanta (HM Publisher, 2023)
Background: Decubitus ulcers are injuries to skin and underlying tissue resulting from prolonged pressure on the skin. There are numbers of surgical methods have been devised over a year for treatment of decubitus ulcers. Double Limberg flap is our procedure of choice, which we present here as our experience. Case presentation: The study describe a 29 years old male with chief complaint is unable to move both limbs. One month before admission the patient admitted that he had been hit by the roof of the chicken coop while cleaning it. After the incident, the patient wan unable to move his legs. The patient also admitted that he was unable to control his urination and bowel movements. The patient also complained that there were ulcers in the buttocks that were caused by being in bed for a long time. At Dr. Mohammad Hoesin General Hospital, the patient is planned to undergo posterior stabilization. After the posterior stabilization is carried out, this patient was planned to have the ulcer closure using a Limberg flap. The double limber flap survived completely. Flap necrosis was not seen in this case. The largest defect covered by this flap. There was no recurrence of pressure sores in this patient in the 6 month follow-up period. Conclusion: The Limberg flap is a fast, accurate and reliable alternative surgical technique utilizing local tissue in treating sacral decubitus ulcer. Limberg flap repair is an effective technique with short learning curve, patient comfort, early healing, and least complications and recurrence rates are the advantages of this procedure.